Molecular dynamics investigation of a model ionic liquid lubricant for automotive applications. (September 2017) - Gkagkas, Konstantinos; Ponnuchamy, Veerapandian; Dašić, Miljan; Stanković, Igor
Abstract: In the current work we present a new modelling approach for simulating meso–scopic phenomena related to lubrication of the piston ring–cylinder liner contact. Our geometry allows a variable confinement gap and a varying amount of lubricant in the gap, while avoiding the squeeze-out of the lubricant into vacuum. We have implemented a coarse grain molecular dynamics description of an ionic liquid as a lubricant which can expand into lateral reservoirs. The results have revealed two regimes of lubrication, an elasto-hydrodynamic one under low loads and one with low, velocity-independent specific friction, under high loads. The observed steep rise of normal forces at small plate-to-plate distances is an interesting behaviour that could potentially be exploited for preventing solid–solid contact and wear. Abstract : Highlights: New efficient MD friction simulation for engineering systems. Continuous lubricant between 2 solids combined with void space for liquid expansion. Stable lubrication layer formation in case of ionic liquid lubricant. Logarithmic dependence of friction force on velocity.